The development of unlabeled probes-high resolution melting (UP-HRM) marker on SAD, IAA27 and ACC genes of oil palm (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saputra TI, Roberdi, Nugroho YA, Artutiningsih W, Purba OS, Maryanto SD, Yono D, Utomo C, Liwang T. 2021. The development of unlabeled probes-high resolution melting (UP-HRM) marker on SAD, IAA27 and ACC genes of oil palm. Biodiversitas 22: 3356-3362. The unlabeled probes-high resolution melting (UP-HRM) marker is a useful tool for detecting of single nucleotide polymorphisms (SNPs). The objectives of this study were to develop UP-HRM markers to differentiate specific SNPs patterns on oil palm. The marker was developed and tested with Elaeis guineensis (Eg), Elaeis oleifera (Eo), Eo x Eg (hybrid), and was validated with 53 individuals of BC1F1 populations ((Eo x Eg) x Eg). Four UP-HRM markers were developed based on 2 SNPs in the stearoyl-acyl-carrier-protein 9-desaturase (EgSAD), 1 SNP in the auxin-responsive protein IAA27-like (EgIAA27), and 1 SNP in the 1-amino cyclopropane-1-carboxylate oxidase (EgACC) genes. The SNP discovery result showed that Eg was represented a reference homozygote genotype, while Eo was represented as an alternative homozygote genotype and the Eo x Eg hybrid was represented as a heterozygote genotype in all genes. The typical UP-HRM melt curve graph was successfully generated. This result was consistent with each genotype model for all four markers. The UP-HRM markers can distinguish each genotype according to the single-pass sequencing results. Furthermore, dendrogram analysis on validation divided 53 BC1F1 samples into three cluster groups.
Keywords: HRM, Interspecific hybrid, Molecular markers, Oil palm, SNPs genotyping.